Providing and depriving a sense of ontological security: EU enlargement in North Macedonia - Jekić, Aleksandar (Journal of Regional Security, 2024)
The paper seems to analyse in which ways EU accession can act as a potential source of ontological (in)security by using the case of North Macedonia. After outlining the social and material environment that constitutes the Macedonian identity and in turn acts as a source of ontological security, a qualitative content analysis of 61 text units that were authored by members of Macedonian parliamentary parties is employed. The sample of texts is thereby centred around two critical situations that contested the social and material environment of the Macedonian identity, namely the announcement of the Bulgarian veto in 2020 and the acceptance of the French proposal in 2022. The results of the analysis demonstrate that EU enlargement can both serve as a source of ontological security and insecurity. While governmental parties see EU membership as a protection of the Macedonian identity, the opposition connects the current enlargement framework to its disappearance. Through support from the public and the low credibility of the enlargement policy, the perceived threat towards the own identity that is articulated by the opposition can further slowdown North Macedonia’s pathways to EU membership. The article, therefore, illustrates how an accession process can become deadlocked due to ontological insecurity of parts of the political elite, underlining the importance of intra-state dynamics for the understanding of cases of ontological security.